Constructing Professional Identity through Virtual Training: Challenges and Resilience of Indonesian English Teachers - Haseng, Husnul Fahimah; Zulfah Fakhruddin; Mujahidah; Ambo Dalle; Abdul Haris Sunubi; Nurfaidah, Sitti (Institut Agama Islam Negeri (IAIN) Kendari, 2026)
As professional development for English teachers increasingly shifts to online environments, virtual training has emerged as a significant yet challenging space for the formation and maintenance of professional identity. While teacher professional identity, resilience, and online professional development have each been widely studied, limited attention has been given to how these areas intersect, particularly within the Indonesian EFL context. This study investigated how Indonesian English teachers constructed their professional identity through participation in virtual training. It focused on the challenges they encountered, the resilience resources they drew upon, and the ways these experiences influenced their professional selves. Using a qualitative design, the study drew on semi-structured interviews with six in-service English teachers who were purposively selected from a virtual training program facilitated by the Regional English Language Office (RELO). The data were analyzed using reflexive thematic analysis. The findings identified four interconnected categories of challenges: technological and infrastructural, institutional and contextual, pedagogical, and psychological and emotional. Rather than serving solely as barriers, these challenges became sites of identity negotiation. Teachers responded by mobilizing both personal resources including motivation, reflection, self-regulation, and emotional competence and external resources, such as family support, institutional encouragement, communities of practice, and a supportive virtual environment. The study concludes that resilience functions as the mechanism through which challenges are translated into processes of professional identity construction. It also highlights the importance of designing virtual professional development that is responsive to context, emotionally supportive, and attentive to teacher identity